Thermodynamic Analysis of a Combined Recompression Supercritical Carbon Dioxide Brayton Cycle With an Organic Flash Cycle for Hybrid Solar-Geothermal Energies Power Generation - Que, Yi; Hu, Zhiming; Ren, Song; Jiang, Zhang (Frontiers in Energy Research, 2022)
Exploring renewable energy is beneficial for ameliorating the energy crisis and reducing environmental emissions. The hybrid utilization of solar and geothermal energies is an effective way to improve the existing energy consumption structure dominated by fossil energy. This paper proposes a novel power generation system composed of a topping recompression supercritical carbon dioxide (sCO2) Brayton cycle and a bottom organic flash cycle (OFC) driven by the hybrid solar-geothermal energies. The sCO2 Brayton cycle is driven by the heat from the solar tower system, and the OFC is driven by a part of the heat from CO2 in the sCO2 Brayton cycle and another part of the heat from the geothermal water. The corresponding energy and exergy analyses of the proposed combined system are presented. The effects of the five main parameters on the system thermodynamic performance are carried out, which are direct radiation intensity, concentration ratio, sCO2 pressure ratio, preheater terminal temperature difference, and flash temperature. Results show that the OFC with R245ca has the highest exergy efficiency among the different four fluids. The energy efficiency and exergy efficiency of the total system are 26.03% and 33.38%, respectively, since the energy losses exist in the heliostat field and central receivers. There observes that through the parametric study the parameters of direct radiation intensity and concentration ratio are larger causing better system thermodynamic performance. Through the thermodynamic analysis, there observes the power cycle subsystem has the largest energy loss, while the central receiver possesses the highest among other subsystems.